The Interplay Between Competition Intensity and Innovation in the Restaurant Business - Rachmawati, Dyna; Bandoro, Andrean Leonardus; Koesmono, Teman (JISR management and social sciences & economics, 2025)
This study examines the intensity of competition in the restaurant industry and explores potential solutions to address it. This study used a qualitative design with a phenomenological approach. The study sample comprised restaurants in Surabaya, Indonesia. The sample includes four restaurant restaurateurs, six restaurant entrepreneurs, and six restaurant consultants as participants. The results of this study indicate that the intensity of competition in the restaurant industry is high, as determined by Porter’s Five Forces analysis. The threat of new entrants and the bargaining power of suppliers were moderate. The threat of the bargaining power of the buyer, product substitution, and existing competitors is high. Most experts suggest that innovation is the key to overcoming intense competition. The study’s findings also reveal that restaurateurs’ orientations are divided into innovation- and cost-oriented approaches. Innovation (cost)-oriented restaurants have characteristics similar to differentiation (cost leadership) competitiveness. This difference in orientation impacts innovation activities aimed at addressing the intensity of competition, which can create deterrence in the face of high competition. This study has both academic and practical implications, suggesting that the innovations implemented should align with the restaurant’s orientation to impact its performance positively.